Inpregnação de madeiras de eucalipto e pinho em processos de polpação alcalina, efeitos da pré-vaporização e da impregnação pressurizada. - Inalbon, Maria Cristina (2005)
The pattern of alkaline impregnation of eucalyptus and pinewood under industrial conditions, i.e. presteaming and pressurized impregnation, is analyzed. Difference between the external and central zones in the log section for 8-year-old Eucalyptus grandis and between earlywood and latewood of 25-year-old Pinus elliotti wood are examined. Profiles of content and concentration of alkali as well as profiles of liquid content and acetyl group content are experimentally determined. Results show that an impregnation front is established inside wood, which separates an intact inner zone from an external swollen zone. After presteaming, an important amount of liquid enters the wood under the pressurized impregnation. Wood is almost saturated by liquid. Earlywood of pine reaches a liquid content of 2.5g/g wood. It is suggested that, at the beginning of the impregnation, the liquid arrives at the core of a chip but the alkali does not. The described characteristics results useful to analyze the effects of variables on the time that is needed for impregnation in an industrial process